Diagnosis of growth hormone deficiency in the paediatric and transitional age. Issue 6 (December 2016) - Chinoy, A.; Murray, P.G.
Abstract : Growth hormone deficiency is a rare cause of childhood short stature, but one for which treatment exists in the form of recombinant human growth hormone. A diagnosis of growth hormone deficiency is made based on auxology, biochemistry and imaging. Although no diagnostic gold standard exists, growth hormone provocation tests are considered the mainstay of diagnostic investigations. However, these must be interpreted with caution in view of issues with variability and reproducibility, as well as the limited evidence-base for cut-off values used to distinguish growth hormone deficient and non-growth hormone deficient subjects. In addition, nutritional and pubertal status can affect results, with no consensus on the role of priming with sex steroid hormones. Difficulties with assays exist both for growth hormone as well as insulin-like growth factor-1. Pituitary magnetic resonance imaging is a useful diagnostic, and possibly prognostic, aid. Although genetic testing is not routine, the discovery of more relevant mutations makes it an increasingly important investigation. Children with growth hormone deficiency are retested biochemically on completion of growth, to assess whether they remain so into adulthood.